Recovery and partial purification of thermophilic β-xylosidase derived from recombinant Bacillus megaterium MS941 by aqueous two-phase system - Hadi, Sofijan; Tan, Joo Shun; Abbasiliasi, Sahar; Mustafa, Shuhaimi; Puspaningsih, Nyoman Tri; Kadkhodaei, Saeid; Ariff, Arbakariya (Taylor & Francis, 2017)
A polymer–salt-based aqueous two-phase system (ATPS) was developed for the effective extraction and purification of extracellular β-xylosidase from the fermentation broth of recombinant Bacillus megaterium MS941. The effect of molecular weight (MW) of polyethylene glycol (PEG), tie-line length (TLL), volume ratio (VR), crude loading and pH on the recovery performance was evaluated. Under the optimal extraction conditions, β-xylosidase was successfully purified up to 23-fold with a recovery yield of 99% in the bottom salt-rich phase at PEG 4,000/potassium phosphate ATPS comprising TLL of 41.8, VR of 2.3, crude loading (CL) of 30% (w/w) at pH 6.